Student competencies in intracurricular learning through project-based learning in Muhammadiyah junior high school - Lise Chamisijatin; Siti Zaenab (Universitas Muhammadiyah Malang, 2024)
This research provides an overview of the application of the Project-based Learning (PjBL) model in intracurricular learning in forming student competencies. The objectives of this research are: (1) Describe the implementation of the PjBL model in intracurricular learning which can improve student competence in a Muhammadiyah junior high school in East Java, (2) Describe the competency achieved by students by implementing the PjBL model in intracurricular learning in a school Muhammadiyah junior high school in East Java, (3) Describe the school's obstacles and solutions in implementing the PjBL model in intracurricular learning at a Muhammadiyah junior high school in East Java. The research method used is descriptive research with a qualitative approach. The instruments in this research include in-depth interviews, observation and documentation studies. This research provides important information regarding the successful implementation of PjBL. All teaching modules have mentioned the implementation of PjBL, but only one teaching module clearly describes the PjBL-based learning steps. The average implementation of the PjBL model is 63% (sufficient category). Most students responded very well to the learning process carried out by the teacher. The range of student scores is 70 to 90. There are several problems and solutions taken by the school in an effort to make the implementation of PjBL successful. The research findings can be an illustration of examples or variations of good practice in implementing the PjBL model in intracurricular learning in implementing the independent curriculum in an effort to build student competency.